Acupuncture for comorbid depression and insomnia in perimenopause: A feasibility patient-assessor-blinded, randomized, and sham-controlled clinical trial - Zhao, Fei-Yi; Zheng, Zhen; Fu, Qiang-Qiang; Conduit, Russell; Xu, Hong; Wang, Hui-Ru; Huang, Yu-Ling; Jiang, Ting; Zhang, Wen-Jing; Kennedy, Gerard A. (Frontiers in Public Health, 2023)
Background and Objective Whilst acupuncture is widely used for treating psychosomatic diseases, there is little high-quality evidence supporting its application in comorbid perimenopausal depression (PMD) and insomnia (PMI) which are common complaints during climacteric. This feasibility, patient-assessor-blinded, randomized, sham-controlled clinical trial addresses this gap by investigating the efficacy and safety of acupuncture on depressed mood and poor sleep in women with comorbid PMD and PMI. Methods Seventy eligible participants were randomly assigned to either real-acupuncture (RA) or sham-acupuncture (SA) groups. Either RA or SA treatment were delivered in 17 sessions over eight weeks. The primary outcomes for mood and sleep were changes on 17-items Hamilton Depression Rating Scale (HAM-D17) and Pittsburgh Sleep Quality Index (PSQI) scores, from baseline to 16-week follow-up. Secondary outcome measures involved anxiety symptoms, perimenopausal symptoms, quality of life, participants’ experience of and satisfaction with the acupuncture treatment. Blood samples were taken to measure reproductive hormone levels. Intention-To-Treat and Per-Protocol analyses were conducted with linear mixed-effects models. The James’ and Bang’s blinding indices were used to assess the adequacy of blinding. Results Sixty-five participants completed all treatment sessions, and 54 and 41 participants completed the eight- and 16-week follow-ups, respectively. At post-treatment and 8-week follow-up, the RA group showed a significantly greater reduction in PSQI scores than the SA group; although the reduction of HAM-D17 scores in RA group was significant, the change was not statistically different from that of SA. There were no significant mean differences between baseline and 16-week follow-up in either HAM-D17 or PSQI in either group. There were no significant between-group differences in serum reproductive hormone levels. All treatments were tolerable and no serious adverse events were reported. Conclusion Acupuncture is safe and can contribute to clinically relevant improvements in comorbid PMD and PMI, with satisfactory short-and medium-term effects. Whether the anti-depressive benefit of acupuncture is specific or non-specific remains to be determined. No evidence was found for any longer-term benefit of acupuncture compared to sham at 16 weeks. Further research is required to elucidate mechanisms underlying the short to medium term effects of acupuncture.